2006
DOI: 10.2133/dmpk.21.324
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Analysis of Micafungin in Japanese Patients with Fungal Infections

Abstract: The object of this analysis was to develop a population pharmacokinetic model of micafungin, a new anti-fungal agent of the echinocandin class, to optimize dosing in Japanese patients with fungal infections. Population pharmacokinetics parameters were determined using NONMEM based on pharmacokinetic data from 198 subjects in seven clinical studies, comprising four phase I, two phase II and one pediatric phase III study. The healthy subjects received intravenous infusion of 2.5-150 mg micafungin. Adult and pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
5
16
1
Order By: Relevance
“…Further investigations in the patients with higher T. bil level may be required. Concerning kidney function, we found that the plasma concentrations of MCFG, were not influenced by the parameters of kidney function as has been reported in population pharmacokinetic study (17) and by Shimoeda et al (16). Although protein binding of MCFG in human serum and plasma is reported to be 99.8%, (13,18) there was no relationship between the plasma concentrations of MCFG and serum albumin levels.…”
Section: Discussionsupporting
confidence: 81%
“…Further investigations in the patients with higher T. bil level may be required. Concerning kidney function, we found that the plasma concentrations of MCFG, were not influenced by the parameters of kidney function as has been reported in population pharmacokinetic study (17) and by Shimoeda et al (16). Although protein binding of MCFG in human serum and plasma is reported to be 99.8%, (13,18) there was no relationship between the plasma concentrations of MCFG and serum albumin levels.…”
Section: Discussionsupporting
confidence: 81%
“…Burn injury affects many organ systems throughout the body, resulting in complex pathophysiological changes, including changes in plasma protein levels (8). In this study, no obvious relationships between the plasma MCFG concentrations and the laboratory parameters for hepatic and renal function, serum albumin, surgical operation, and continuous hemodiafiltration were observed (Table 1), similar to data in previous reports (7,9,11,16). On the other hand, the distribution volume in patients with burns is known to be altered by changes in the extracellular fluid volume (8).…”
supporting
confidence: 90%
“…In a population-based pharmacokinetic analysis using pediatric and adult patients, neither hematocrit nor serum albumin concentration was selected as a contributory factor for total body clearance of MCFG (Tabata et al 2006). The present study therefore provided experimental evidence using a rat model supporting the previous clinical findings.…”
Section: Discussionsupporting
confidence: 65%